Ocrepeira klamt sp. n. (Araneae: Araneidae), a novel spider species from an Andean páramo in Colombia. - Charlotte Hopfe (PLoS ONE, 2020)
Herein we describe Ocrepeira klamt sp. n. (Araneae: Araneidae), a new orb-weaving spider species from a Colombian páramo, which was formerly inaccessible for scientific studies due to decades long armed conflicts. Both, phenotypic and molecular data are used to confirm genus affiliation, and the new species is placed into phylogenetic context with other araneid spiders. Morphological characteristics and ecological notes of Ocrepeira klamt sp. n. are reported together with the sequence of the barcoding region of cytochrome c oxidase subunit I (COI) to provide a comprehensive description of the spider, facilitating future identification beyond taxonomic experts. With this study we contribute to the taxonomic knowledge that is required to inventory the hyper diverse yet threatened ecosystem of the Colombian páramos.